Core temperature measurement: methods and current insights - Moran, D. S.; Mendal, L. (Sports Medicine, 2002)
Climatic injuries, including hypothermia, hyperthermia and heat stroke, are common in many sports activities. Body core temperature (T(c)) measurement for the sportsperson can influence individual performance and may help to prevent injuries. Monitoring internal body T(c) accurately requires invasive methods of measurement. The mercury thermometer, most commonly used to measure oral temperature (T(oral)), has been almost exclusively the only instrument for measuring T(c) since the 18th century. Rectal (T(re)) and oesophageal temperatures (T(oes)) have been the most preferred measurement sites employed in thermoregulatory investigations. However, these measurement sites (T(re), T(oes), T(oral)), and the methods used to measure T(c) at these sites, are not convenient. T(oral) measurements are not always possible or accurate. T(oes) is undesirable because of the difficulty of inserting the thermistor, irritation to nasal passages and general subject discomfort. T(re) is not suitable under many circumstances as it is labour intensive and has a prolonged response time. However, T(re) remains the most accurately available method for monitoring T(c) in thermal illness that occurs during sports activities. In addition, T(re) and T(oes) require wire connections between the thermistor and the monitoring device. The purpose of this paper is to review the various existing methods of T(c) measurements in order to focus on the breakthrough needed for a simple, noninvasive, universally used device for T(c) measurement which is essential for preventing climatic injuries during sports events.